Chemotherapeutic Drugs Induced Symptom Distress Among Pediatric Cancer Patients: Pharmaceutical Science-Pediatric Mental Health - Jeayareka, J; Raman, K; Singh, Lokesh Kumar; Jagzape, Tushar Bharat (International Journal of Life Science and Pharma Research, 2022)
Pediatric cancer treatment includes several chemotherapeutic drugs in combination with adequate supportive management. Symptom distress among pediatric cancer patients on chemotherapy interferes with treatment compliance. Poorly managed distress leads to the decline of the child’s ability physically and mentally and deteriorates the quality of life. This paper shows the effect of chemotherapeutic drugs induced symptom distress, and the effect of early diagnosis in the management and improvement in the quality of life of pediatric cancer patients. For this study60, pediatric cancer patients aged between 10 to 18 years including both the gender were chosen using purposive sampling. Using the M.D. Anderson symptom inventory the symptom distress experienced by the pediatric cancer patients was assessed. The present quantitative cross-sectional study was conducted at the AIIMS, Raipur. The data were analyzed using the descriptive Statistical Package for Social Science Version 16 (SPSS 16). The categorical data was analyzed using chi –square test and the cut off p-value at ≤0.05. Among, the pediatric cancer patients 77.65% (SD 18.85) were experiencing severe symptom distress when on chemotherapy. Whereas 53.65 %( SD 9.63). of them experiencing the symptoms those disturb their activities of daily living in the last twenty four hours at p-value of ≤0.05. There is a need for an adequate support system from the school, social relationship, siblings, and health care team for improving the quality of life of pediatric cancer patients. Animal facilitated therapy, artistics expressions, medical play, procedural education, well organized home bound or school programs help the pediatric cancer patients to manage the symptom distress, thereby improving the treatment outcome. The specific supportive chemotherapeutic management is essential for the pediatric cancer patient’s treatment compliance and prognosis. The health care team, especially nurses play a vital role in early detection of chemotherapeutic agents induced symptom distress and its management.